If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3m + 8m + 5 = -105 Reorder the terms: 5 + 3m + 8m = -105 Combine like terms: 3m + 8m = 11m 5 + 11m = -105 Solving 5 + 11m = -105 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 11m = -105 + -5 Combine like terms: 5 + -5 = 0 0 + 11m = -105 + -5 11m = -105 + -5 Combine like terms: -105 + -5 = -110 11m = -110 Divide each side by '11'. m = -10 Simplifying m = -10
| (x-12)(4x+3)=0 | | 4(x+2)=14-2(3-x) | | 9-3n-5= | | -np=wp-g | | 4n+7=9+2n | | 14(x+2)=14-2(3-x) | | x^2-16x-5= | | -2+8x=2x+10 | | 7-5x+11=-7(x+10)-12(x-5) | | 7y^2-y-2=0 | | 15=x+2x+4x+1 | | 2(5-4v)+2V=-54 | | x^2+26x+52=-53 | | qp+k=sp | | 4sec-3=5 | | (3x+4)*(3x+4)=0 | | 6=5m-3 | | 18+3=-3(2x-7) | | 23-4x=57 | | 2.66=u-2.33 | | 3x+5x+6x-1+2x+4=85 | | X^4+20x^2+35=0 | | -5+3x=5x-9 | | log(y^6x)= | | 3+7p=7p+2+1 | | 2n+5-3p+4n= | | ap+bp=g | | 9(a+2)+6(a-11)=1+11a+a-10 | | 4=2x+1+x | | 2k=27 | | 6w+1=1 | | 6x-11=4x+13 |